Allergen‐specific immunoglobulin E in sera of horses affected with insect bite hypersensitivity, severe equine asthma or both conditions. (6th December 2018) - Verdon, Maëva; Lanz, Simone; Rhyner, Claudio; Gerber, Vinzenz; Marti, Eliane
Abstract : Background: Genetic, epidemiologic, and clinical evidence suggests that, in horses, there are manifestations of hypersensitivity that can occur together. Objectives: To investigate whether concurrent insect bite hypersensitivity (IBH) and severe equine asthma (EA) is associated with higher allergen‐specific and total serum immunoglobulin E (IgE) concentrations than only EA or IBH. Animals: Healthy control horses (C, n = 40), horses with IBH (IBH, n = 24), severe EA (EA, n = 18), and both conditions (IBH/EA, n = 23) were included. Methods: In our retrospective comparative study, sera from horses with signs of severe EA, IBH, and control animals were used. IgE specific for 15 recombinant (r) allergens as well as total serum IgE concentrations were measured by enzyme‐linked immunosorbent assay. Results: Group IBH (median sum r‐ Culicoides IgE: optical density at 405 nm [OD405 ] = 3.54 [0.48‐15.07]) and group IBH/EA (OD405 = 4.55 [0.46‐17.15]) had significantly ( P < .001) higher IgE against Culicoides r‐allergens than groups C (OD405 = 0.44 [0.21‐2.05]) and EA (OD405 = 0.6 [0.2‐2.9]). There were no significant ( P > .05) differences between group IBH and group IBH/EA. No significant differences among the groups were found for the other r‐allergens or total serum IgE concentration. Compared to controls, horses with severe IBH had significantly increased IgE concentration to 5 Culicoides r‐allergens ( P < .05), whereas horses with moderate IBH had significantly increased IgE concentration to only 3 Culicoides r‐allergens ( P < .05). Conclusions and Clinical Importance: Susceptibility of IBH‐affected horses to develop EA is likely not associated with IgE‐mediated immune reactions but with other immunopathological mechanisms.